Pengaruh Bahan Ajar Muatan Lokal Bencana Alam di Bengkulu Terhadap Hasil Belajar Siswa di Kelas V - Princess Mozart Della Islami; Herman Lusa; Dalifa Dalifa (JURIDIKDAS, 2018)
This research is to know the influence of local content teaching materials of natural disasters in Bengkulu on the results of the students of V grade of public elementary school 73 Bengkulu city. This research is a quantitative research. The research design used was Pre-Experimental Design with Pretest-Posttest Control Design Matching Type, in which two tests were taken before and after treatment in the experimental class and control class. Subjects in this study were the students of V grade of public elementary school 73 Bengkulu city consisting of VA class as experimental class and VB class as control class. The research instrument used is the multiple choice given through pretest (before the learning takes place) and posttest (after the learning takes place). Data of this research are analyzed by using descriptive and inferential analysis that is t-test. From the results of the study. The result of tcount 2.31 and ttable 2.01. So with tcount (2.31)> ttable (2.01). The value of tcount obtained is greater than the value of ttable it can be concluded the existence of the influence of local content teaching materials of natural disasters in Bengkulu on the results of student learning in V grade of public elementary school 73 Bengkulu city.